Effect of Staggered Contour Trenches and Hillside Ditches on surface runoff and soil loss on steep slopes in shaded coffee (Coffea arabica), Costa Rica - Palominos Rizzo, María Teresa (2024)
Soil erosion is one of the main causes of soil degradation and an important environmental problem, often accelerated by human activities. Different types of soil and water conservation measures (SWCM) have been implemented in worldwide to control soil loss, such as Staggered Contour Trenches (SCT) and Hillside ditches (HD) which are recommended in topographies up to 40 % slope. This study measured the effects of STC and HD, on surface runoff, soil loss, exposed of organic matter and soil moisture content, in a shaded coffee crop with steep slopes in an Entisol soil. Nine runoff plots were installed in Llano Brenes, Costa Rica, in the upper basin of the Jesús María River in a study area with slopes between 50 and 71 ± 7.92 %. We conclude that this study could make an important contribution to research on the use of SWCM on tropical soils with slopes greater than 50 %. Due to the non-compliance of assumptions, a logarithmic transformation of the data was used, and they were evaluated using the Kruskal-Wallis one-way nonparametric test. Spearman correlation and linear regressions were used to assess the effect of the precipitation and intensity in the soil loss and runoff in each treatment. The amount of organic matter exposed by soil removal was not statistically different between HD and SCT, but both were different to the control (R2 = 0.81, P < 0.05). Spearman correlation analysis showed the rainfall depth contributed more to runoff depth (HD R = 0.62; SCT R = 0.62; Control R = 0.60; P < 0.001) and soil loss (HD R = 0.50; STC R = 0.53; Control R = 0.50; P < 0.001) than other variables. Regression analysis showed that runoff and soil loss were significant (P < 0.05) and positively correlated with rainfall depth for each treatment. In this study, HD was shown to be efficient in erosion control on steeper slopes. HD helped reduce soil loss compared to the control, by 88 % in 2018 and 83 % in 2019. HD also reduced runoff generation by 55 % in 2018 and 60 % in 2019 compared to the control. While SCT was not statistically different in the generation of surface runoff and soil loss compared to the control.